Establishing a new index of muscle cross-cectional area and its relationship with isometric muscle strength - Akagi, R.; Kanehisa, H.; Kawakami, Y.; Fukunaga, T. (The Journal of Strength and Conditioning Research, 2008)
The present study aimed i) to establish an index of muscle cross-sectional area (CSA) based on muscle thickness and circumference through a comparison with muscle CSA determined by magnetic resonance imaging (MRI), and ii) to examine the relationships between muscle strength and the index determined at rest and during the maximal isometric contraction. The muscle CSA of elbow flexors at 60% of the upper arm length (CSA60) and the maximal CSA of elbow flexors (CSAmax) were measured using MRI in 26 men and 8 women. The muscle thickness (MT) of elbow flexors and the circumference (C) of upper arm at 60% of the upper arm length were measured using ultrasonography and anthropometry, respectively, in 29 men and 9 women. The measurements of MT and C were performed in the resting (MTr and Cr) and contracted condition (MTm and Cm), where the subjects performed maximal voluntary contraction (MVC) of isometric elbow joint flexion. The torque developed during MVC was converted into the muscle force (F) of elbow flexors. The MTr x Cr was significantly correlated both with CSA60 and CSAmax (P < 0.001). The F was significantly correlated with MTm x Cm (r = 0.847, P < 0.001) and MTr x Cr (r = 0.839, P < 0.001). However, stepwise multiple regression analysis selected only MTm x Cm as a significant contributor for estimating F. The present study indicates that MT x C reflects muscle CSA, and can be an index for assessing muscle CSA. In addition, the findings obtained here showed a possibility that MT x C during MVC is more closely related to F than that at rest.